Prevalence of diabetes distress and associated factors among patients with diabetes using antihypertensive medications in community health centres in Bandung City, Indonesia - Sofa Dewi Alfian; Imam A. Wicaksono; Norisca A. Putri; Rizky Abdulah (Pharmaciana, 2021)
Diabetes distress is common among patients with type 2 diabetes mellitus (T2DM), which remains unrecognized in primary care settings. A higher level of diabetes distress was found among T2DM patients with comorbidities. The objectives of this study are to assess the prevalence rate of diabetes distress and its association with sociodemographic factors among T2DM patients using antihypertensive medication in Bandung City, Indonesia. An observational cross-sectional survey was performed in six community health centres in Bandung City, Indonesia, among T2DM patients aged at least 18 years who were using antihypertensive medications. Diabetes distress subscales (emotional, regimen, interpersonal, and physician-related distress) were evaluated using the validated Diabetes Distress Scale. Pearson χ2 and Mann–Whitney tests were performed to assess the associations of patients’ sociodemographic factors (age, gender, insurance type, education, and duration since diagnosed with diabetes and hypertension) with diabetes distress. Of 105 patients who participated and completed the survey (response rate 93.8%), most of them were female and were aged 60-69 years. A total of 38 patients (36.2%) had moderate-high diabetes distress with emotional (56.2%) and regimen (53.3%) distress as the most commonly reported distress. Moderate-high emotional and regimen diabetes distress were significantly higher among the elderly (p 0.014) and patients who could not afford to pay the health insurance premium (p 0.012). Emotional and regimen distress as dominant forms of diabetes distress was observed among T2DM patients using antihypertensive medications. A routine diabetes distress assessment is needed in T2DM patients with comorbidity in primary care settings.